2015
DOI: 10.1038/sc.2015.147
|View full text |Cite|
|
Sign up to set email alerts
|

Text input speed in persons with cervical spinal cord injury

Abstract: Study design: This is a prospective clinical study. Objectives: The objectives of this study were to determine text input speed (TIS) in persons with cervical spinal cord injury (SCI) and to study the influence of personal characteristics and type of computer access device on TIS. Setting: This study was conducted in the Rehabilitation Department, Garches, France. Methods: People with cervical SCI were included if their level of injury was between C4 and C8 Asia A or B, and if they were computer users. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This may be due to the few people with a level of SCI above C4 in our study. Nevertheless, such devices may make Internet use easier [23,24]. May be the accessibility options of modern computers, such as standard voice activation and touch screens, have limited the need for special assistive devices for most people with a limited hand function.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the few people with a level of SCI above C4 in our study. Nevertheless, such devices may make Internet use easier [23,24]. May be the accessibility options of modern computers, such as standard voice activation and touch screens, have limited the need for special assistive devices for most people with a limited hand function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of speech-recognition software and head or mouth controls was low, probably because few people with C4 SCI were included in the study. In the United States, a study [5, 6] conducted between 2003 and 2006 showed that only 35% of participants with tetraplegia used an assistive device to enable computer and Internet use, despite the ability of these devices to facilitate Internet use [7, 8]. These studies highlight the need for novel interfaces that compensate for loss of body functions by utilizing other available input sources for control [7].…”
Section: Introductionmentioning
confidence: 99%